Pressure overload inhibits glucocorticoid receptor transcriptional activity in cardiomyocytes and promotes pathological cardiac hypertrophy. (May 2019) - Matsuhashi, Tomohiro; Endo, Jin; Katsumata, Yoshinori; Yamamoto, Tsunehisa; Shimizu, Noriaki; Yoshikawa, Noritada; Kataoka, Masaharu; Isobe, Sarasa; Moriyama, Hidenori; Goto, Shinichi; Fukuda, Keiichi; Tanaka, Hirotoshi; et al.
Abstract: Glucocorticoid receptor (GR) is abundantly expressed in cardiomyocytes. However, the role of GR in regulating cardiac hypertrophy and heart failure in response to pressure overload remains unclear. Cardiomyocyte-specific GR knockout (GRcKO) mice, mineralocorticoid receptor (MR) knockout (MRcKO), and GR and MR double KO (GRMRdcKO) mice were generated using the Cre-lox system. In response to pressure overload, GRcKO mice displayed worse cardiac remodeling compared to control (GR f/f ) mice, including a greater increase in heart weight to body weight ratio with a greater increase in cardiomyocytes size, a greater decline in left ventricular contractility, and higher reactivation of fetal genes. MRcKO mice showed a comparable degree of cardiac remodeling compared to control (MR f/f ) mice. The worse cardiac remodeling in pressure overloaded GRcKO mice is not due to compensatory activation of cardiomyocyte MR, since pressure overloaded GRMRdcKO mice displayed cardiac remodeling to the same extent as GRcKO mice. Pressure overload suppressed GR-target gene expression in the heart. Although plasma corticosterone levels and subcellular localization of GR (nuclear/cytoplasmic GR) were not changed, a chromatin immunoprecipitation assay revealed that GR recruitment onto the promoter of GR-target genes was significantly suppressed in response to pressure overload. Rescue of the expression of GR-target genes to the same extent as sham-operated hearts attenuated adverse cardiac remodeling in pressure-overloaded hearts. Thus, GR works as a repressor of adverse cardiac remodeling in response to pressure overload, but GR-mediated transcription is suppressed under pressure overload. Therapies that maintain GR-mediated transcription in cardiomyocytes under pressure overload can be a promising therapeutic strategy for heart failure. Highlights: Cardiac GR activity suppresses pathological hypertrophy under pressure overload. Cardiomyocyte MR plays a lesser role in cardiac remodeling than cardiomyocyte GR. Pressure overload suppressed GR-mediated gene expression. Rescue of GR transcription prevents pathological hypertrophy under pressure overload.